Hydrogenation of the Exocyclic Olefinic Bond at C-16/C-17 Position of ent-Kaurane Diterpene Glycosides of Stevia rebaudiana Using Various Catalysts - Chaturvedula, Venkata Sai Prakash (Molecular Diversity Preservation International (MDPI), 2013)
Catalytic hydrogenation of the exocyclic double bond present between C16 and C17 carbons of the four ent-kaurane diterpene glycosides namely rebaudioside A, rebaudioside B, rebaudioside C, and rebaudioside D isolated from Stevia rebaudiana has been carried out using Pt/C, Pd(OH)(2), Rh/C, Raney Ni, PtO(2), and 5% Pd/BaCO(3) to their corresponding dihydro derivatives with 17α and 17β methyl group isomers. Reactions were performed using the above-mentioned catalysts with the solvents methanol, water, and ethanol/water (8:2) under various conditions. Synthesis of reduced steviol glycosides was performed using straightforward chemistry and their structures were characterized on the basis of 1D and 2D NMR spectral data, including a comparison with reported spectral data.